ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN FINTECH PINJAMAN ONLINE PADA GENERASI Z - Gustriani Putri, Tamiya; Nuryatno Amin, Muhammad (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this research activity is to determine the effect of perceived risk and perceived trust on behavioral intention in using online loan fintech with perceived ease of use as a moderating variable. This study uses primary data from the results of the questionnaire distributed. The sample technique chosen in this study is to utilize purposive sampling. The total number of samples in this study was 100 samples. The analysis method used in this study is multiple regression analysis. The results of this study are perceived risk has no positive and significant effect on behavioral intention, perceived trust has a positive and significant effect on behavioral intention, perceived ease of use does not moderate the effect of perceived risk on behavioral intention, and perceived ease of use does not moderate the effect of perceived trust on behavioral intention.